Trade Liberalization and Its Effects on the Economic Growth of Bangladesh: An Empirical Analysis - Majumder, Shapan Chandra; Rana, Md. Masud (American Journal of Trade and Policy, 2016)
The objective of this paper is to assess the effectiveness of the trade policy on Bangladesh economy between the periods 1990 to 2010. This research analyzes the achievements of the economy regarding the important variables such as growth of GDP, export, import, exchange rate, terms of trade, and foreign reserve after the trade liberalization in 1990s. The study demonstrates that the inward policy of the trade liberalization reduces the import while the forward policy increases the employment, production, and export. Finally, liberalization policy improves overall economic indicators as GDP per capita, FDI, and remittances have been growing up since pre-liberalization. The study shows that both export and import have increased noticeably since liberalization, with import rising faster than export in the period immediately after liberalization.